Joyland - King, Stephen, 1947- (Hard Case Crime, 2013)
Set in a small-town North Carolina amusement park in 1973, Joyland tells the story of the summer in which college student Devin Jones comes to work as a carny and confronts the legacy of a vicious murder, the fate of a dying child, and the ways both will change his life forever.